2022
DOI: 10.3390/molecules27134255
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Amyloid a Impaired Structural Stability of High-Density Lipoproteins (HDL) and Apolipoprotein (Apo) A-I and Exacerbated Glycation Susceptibility of ApoA-I and HDL

Abstract: Human serum amyloid A (SAA) is an exchangeable apolipoprotein (apo) in high-density lipoprotein (HDL) that influences HDL quality and functionality, particularly in the acute phase of inflammation. On the other hand, the structural and functional correlations of HDL containing SAA and apoA-I have not been reported. The current study was designed to compare the change in HDL quality with increasing SAA content in the lipid-free and lipid-bound states in reconstituted HDL (rHDL). The expressed recombinant human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The change in WMF originates from Trp in apoA-I because CIGB-258 has no Trp. Interestingly, an increase in SAA content in the rHDL containing apoA-I accelerated apoA-I glycation [ 14 ], but the current and previous results showed that an increase of CIGB-258 content in rHDL containing apoA-I resulted in the remarkable inhibition of apoA-I and HDL glycation [ 5 , 6 ]. As shown in Figure 5 , proteins and amino acids glycated through CML treatment exhibited dynamic characteristics, as microorganisms are capable of breaking down these compounds [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The change in WMF originates from Trp in apoA-I because CIGB-258 has no Trp. Interestingly, an increase in SAA content in the rHDL containing apoA-I accelerated apoA-I glycation [ 14 ], but the current and previous results showed that an increase of CIGB-258 content in rHDL containing apoA-I resulted in the remarkable inhibition of apoA-I and HDL glycation [ 5 , 6 ]. As shown in Figure 5 , proteins and amino acids glycated through CML treatment exhibited dynamic characteristics, as microorganisms are capable of breaking down these compounds [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, the incorporation of CIGB-258 could increase the particle size of rHDL with a more stabilizing tertiary structure of apoA-I against urea-induced denaturation, suggesting that adding the peptide could enhance the apoA-I stability. Many studies showed that the incorporation of apolipoproteins, such as apoA-II, apoC-III, serum amyloid A (SAA)-1, and α-synuclein (α-syn), in rHDL, resulted in a negative change in the structural stability and functionality [ 14 , 16 , 27 ]. The addition of apolipoprotein A-II (apoA-II) in rHDL containing apoA-I resulted in an almost 50% displacement of apoA-I, around an apoA-I:apoA-II molar ratio of 1:1, resulting in the destabilization of apoA-I and modulation of lecithin:cholesterol acyltransferase (LCAT) activity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In case of an inflammatory response and in atherosclerosis, acute phase proteins such as serum amyloid a (particularly SAA-1), which is secreted by the liver, associates with HDL and modifies its function. Depending upon the concentration and the range of the acute phase response, SAA can displace ApoA-I from the HDL particles, thereby altering the structure and protective properties of HDL [ 112 ].…”
Section: High-density Lipoproteins Are Self-assembling Nanoparticlesmentioning
confidence: 99%